Economic development and material use: Evidence from international panel data - Frank Pothen; Heinz Welsch (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2017)
Between 1990 and 2008, many industrializing countries have experienced tremendous economic growth, which coincided with a substantial increase in the use of materials. That poses the question how a continued economic convergence of developing nations will affect the use of biomass, fossil fuels, and minerals. Building on the Environmental Kuznets Curve hypothesis, this study investigates whether material use reaches a maximum at a certain level of economic development and declines in income thereafter. Two indicators operationalize material use. Domestic Material Consumption (DMC) measures the apparent use of materials in a country. The Material Footprint (MFP) quantifies all materials extracted to produce a country's final demand, including materials embodied in imports. Employing a panel consisting of 144 countries, initial estimations results suggest an S-shaped (cubic) relationship between GDP per capita and material use, but the relationship is monotonically positive over most of the income range. The coefficients of the cubic model tend to become nonsignificant once endogeneity and non-stationarity are accounted for. A linear specification yields a significant (positive) coefficient irrespective of the estimation method and can thus be considered a satisfactory approximation to the income-material use relationship. The linear models that account for endogeneity and non-stationarity suggest a greater income-materials elasticity for MFP than for DMC. The long-run income elasticity is estimated to be 0.562 for DMC and 0.752 for MFP.
Keywords: C36; O13; Q32; 330; Economic Development; Material Use; Material Footprint; Environmental Kuznets Curve; Economic Transformation